Examining the effectiveness of phishing filters against DNS based phishing attacks. (13th July 2015) - Purkait, Swapan
Abstract : Purpose: – This paper aims to report on research that tests the effectiveness of anti-phishing tools in detecting phishing attacks by conducting some real-time experiments using freshly hosted phishing sites. Almost all modern-day Web browsers and antivirus programs provide security indicators to mitigate the widespread problem of phishing on the Internet. Design/methodology/approach: – The current work examines and evaluates the effectiveness of five popular Web browsers, two third-party phishing toolbar add-ons and seven popular antivirus programs in terms of their capability to detect locally hosted spoofed websites. The same tools have also been tested against fresh phishing sites hosted on Internet. Findings: – The experiments yielded alarming results. Although the success rate against live phishing sites was encouraging, only 3 of the 14 tools tested could successfully detect a single spoofed website hosted locally. Originality/value: – This work proposes the inclusion of domain name system server authentication and verification of name servers for a visiting website for all future anti-phishing toolbars. It also proposes that a Web browser should maintain a white list of websites that engage in online monetary transactions so that when a user requires to access any of these, the default protocol should always be HTTPS (Hypertext Transfer Protocol Secure), without which a Web browser should prevent the page from loading.